Blue ribbon baking from a redneck kitchen - Bryson, Francine (Clarkson Potter/Publishers, 2014)
Bryson shares her sought-after recipes and tips, full of her down-home Southern charm and sass. You'll bake up award-winning pies and irresistible treats that will make the round in your church group, bridge club, and moms group for years.